2022
DOI: 10.1055/a-1847-2820
|View full text |Cite
|
Sign up to set email alerts
|

New method for real-time visualization and quantitative characterization of early colorectal cancer in endoscopy: a pilot study

Abstract: Background: Endoscopic optical diagnosis is crucial to the therapeutic strategy in early gastrointestinal cancer. It accurately (> 85%) predicts pT category based on micro surface (SP) and vascular patterns (VP). However, inter-observer variability is a major problem. We have visualized and digitalized the graded irregularities based on bioinformatically enhanced quantitative endoscopic image analysis (BEE) of high definition white light images. Methods: In a pilot study on 26 large colorectal lesions (LCL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Because in clinical, subjects received allogenic bone marrow transplants detected almost no transfer of the donor mitochondria DNA (mtDNA) to the host mtDNA fraction in epithelial, connective, or skeletal muscle tissues, even exposure to the donor mtDNA in EV fractions for years (Tarnopolsky et al, 2020). In addition, studies showed that mitochondria mainly contain in larger EV (250 nm) rather than sEVs (100 nm), although EV (250 nm) contain all parts of mitochondria, their independent functionality inside EV cannot be confirmed due to methodological deficiencies (Wagner et al, 2022;Zorova et al, 2022).…”
Section: Mitochondria Containing In Bmmsc-evsmentioning
confidence: 99%
“…Because in clinical, subjects received allogenic bone marrow transplants detected almost no transfer of the donor mitochondria DNA (mtDNA) to the host mtDNA fraction in epithelial, connective, or skeletal muscle tissues, even exposure to the donor mtDNA in EV fractions for years (Tarnopolsky et al, 2020). In addition, studies showed that mitochondria mainly contain in larger EV (250 nm) rather than sEVs (100 nm), although EV (250 nm) contain all parts of mitochondria, their independent functionality inside EV cannot be confirmed due to methodological deficiencies (Wagner et al, 2022;Zorova et al, 2022).…”
Section: Mitochondria Containing In Bmmsc-evsmentioning
confidence: 99%
“…Despite the suspicious morphology of the 3 × 2 cm lesion, we decided not to resect it following visualization of dense and regular vascular and surface patterns obtained by the BEE variables “density” and “non-uniformity coefficient” ( Fig. 1 ) 1 . Accordingly, multiple targeted biopsies showed chronic inflammation and fibrosis, without dysplasia.…”
Section: Figmentioning
confidence: 99%
“…variables "density" and "non-uniformity coefficient" (▶ Fig. 1) [1]. Accordingly, multiple targeted biopsies showed chronic inflammation and fibrosis, without dysplasia.…”
mentioning
confidence: 96%
See 1 more Smart Citation